Geranyl Flavonoid Derivatives from the Fresh Leaves of Artocarpus communis and Their Anti-inflammatory Activity - Hsu, Chin-Lin; Chang, Fang-Rong; Tseng, Pei-Yu; Chen, Yi-Fen; El-Shazly, Mohamed; Du, Ying-Chi; Fang, Song-Chwan (Planta Medica, 2012)
Breadfruit (Artocarpus communis) is a widely distributed crop in tropical and subtropical regions of the world. It is used in Southeast Asia and India to treat several inflammatory disorders. The aim of this study was to investigate the presence of anti-inflammatory flavonoids in A. communis leaves. Three new geranyl flavonoids, arcommunol C (1), arcommunol D (3), and 5′-geranyl-3,4,2′,4′-tetrahydroxychalcone (5), together with four known compounds, prostratol (2), arcommunol E (4), 3′-geranyl-3,4,2′,4′-tetrahydroxydihydrochalcone (6), and 3′-geranyl-3,4,2′,4′-tetrahydroxychalcone (7), were isolated from the leaves of A. communis. Compound 4 was isolated for the first time from natural sources. The anti-inflammatory activity of the isolated compounds (1–7) was evaluated by determining their inhibitory activity on the production of proinflammatory mediators in lipopolysaccharide (LPS)-activated RAW 264.7 murine macrophage cells. Compounds 2, 3, and 4 suppressed the LPS-induced production of nitric oxide (NO) in RAW 264.7 cells with IC50 values of 8.13 ± 0.17, 18.45 ± 2.15, and 22.74 ± 1.74 µM, respectively. Furthermore, 2 decreased lipopolysaccharide (LPS)-mediated induction of protein expressions of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) in RAW 264.7 cells. It was also found that 2 suppressed LPS-induced phosphorylation of JNK and p38 mitogen-activated protein kinase (MAPK) signaling.
Keywords: Artocarpus communis (Moraceae); geranyl flavonoids; tetrahydroxychalcone; anti-inflammatory; lipopolysaccharide activated RAW 264.7 murine macrophage cells